Regionale Verteilung von Schutzgebieten in Deutschland: Eine empirisch gestützte Bewertung der räumlichen Implikationen des Natur- und Landschaftsschutzes per Ordnungsrecht; Regional Allocation of Conservation Areas in Germany - An Empirically Based Evaluation of Spatial Implications by Law and Order Nature Conservation Policy - Guido Urfei (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– The following analysis leads to an empirically based ranking, which embodies political decision makers to evaluate the necessity of horizontal co-ordination for different issues concerning nature and landscape conservation. First of all the relevant German law and order as well as its spatial conservation categories will be explained (Chapter 2). Secondly the conclusions concerning the spatial inhomogeneity of conservation areas and their implications to environmental-policy are substantiated by the principles of the economic theory of environmental federalism (Chapter 3). Thirdly the definition of suitable concentration indices follows, their quantification for examples of conservation categories (Chapter 4), and the draw up of political recommendations, which are based on these results (Chapter 5).
Keywords: 330; Umweltpolitik; Föderalismus; Naturschutz; Naturschutzgebiet; Räumliche Verteilung; Umweltrecht; Deutschland